District-Level Training and Dissemination of Seasonal Rainfall Forecast - Umer, Yakob; Wapamesa, A; Makungwe, M.; Mwase, R.; Chongo, T. (2025)
The workshop on the review and dissemination of the 2024/2025 and 2025/2026 seasonal rainfall forecasts brought together key agricultural and meteorological stakeholders, including extension officers, district agricultural coordinators, and representatives from the Zambia Meteorological Department (ZMD) and the International Water Management Institute (IWMI). The primary objective was to train the trainers and disseminate the 2025/26 seasonal rainfall forecast at the Chisamba district, central province, Zambia The workshop employed a combination of participatory and interactive methodologies to ensure effective knowledge transfer and understanding of seasonal rainfall forecasts. The workshop brought 70 key provincial and district stakeholders, 16 of these were camp extension officers. The 16 trained extension officers pledged to disseminate the information to 60 farmers each, as such they will reach about 960 farmers before 30th October. While on the second day 160 farmers were reached. Presentations highlighted how seasonal forecasts are produced, interpreted, and localized from regional to district levels, with emphasis on understanding the role of major climate drivers such as the El Niño–Southern Oscillation (ENSO) and the Indian Ocean Dipole (IOD). Dissemination activities at camp and community levels demonstrated farmers’ ability to understand and apply forecast information when communicated through participatory and localized methods, including the use of vernacular languages and visual aids. Moreover, in partnership with National Agricultural Information Services (NAIS) over 5000 farmers will be reached through broadcast media (radio and television) and social media, in all the 7 official local languages. Overall, the initiative enhanced the link between scientific climate information and farmer decision-making, laying a foundation for improved climate-smart agricultural practices in Chisamba District and beyond.